2006
DOI: 10.1063/1.2393243
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of electrostatic solvation energy on dielectric constants in Poisson-Boltzmann calculations

Abstract: The Poisson-Boltzmann equation gives the electrostatic free energy of a solute molecule (with dielectric constant epsilon(l)) solvated in a continuum solvent (with dielectric constant epsilon(s)). Here a simple formula is presented that accurately predicts the electrostatic free energy for all combinations of epsilon(l) and epsilon(s) from the calculation on a single set of epsilon(l) and epsilon(s) values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…More recently, the combination formula (4.13) was proposed to incorporate the effect of dielectric environments; this formula is extremely precise for sphere-like shapes and also very accurate for arbitrary geometries after introducing a correction parameter. Recently, Still's equation was treated by introducing a scaling formula [177, 187] in order to incorporate the dependence of dielectrics.…”
Section: Generalized Born Methodsmentioning
confidence: 99%
“…More recently, the combination formula (4.13) was proposed to incorporate the effect of dielectric environments; this formula is extremely precise for sphere-like shapes and also very accurate for arbitrary geometries after introducing a correction parameter. Recently, Still's equation was treated by introducing a scaling formula [177, 187] in order to incorporate the dependence of dielectrics.…”
Section: Generalized Born Methodsmentioning
confidence: 99%
“…We found that these dependences can be modeled accurately by a scaling formula. 41 Based on that formula, the result of Eq. ͑1͒ is scaled to…”
Section: A Gbrmentioning
confidence: 98%
“…The 55 test proteins have been used in our previous studies to find an empirical dependence of Δ G solv on solute and solvent dielectric constants 21 and to develop GB methods as substitutes of the linearized and full PB equation. 48,49 These proteins were collected from the Protein Data Bank (http://www.rcsb.org/pdb) using the following criteria: sequence identity less than 10%, resolution better than 1.0 Å, and number of residues less than 250.…”
Section: Calculation Detailsmentioning
confidence: 99%